2019
DOI: 10.1186/s41181-019-0058-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular imaging of multiple sclerosis: from the clinical demand to novel radiotracers

Abstract: Background Brain PET imaging with different tracers is mainly clinically used in the field of neurodegenerative diseases and brain tumors. In recent years, the potential usefulness of PET has also gained attention in the field of MS. In fact, MS is a complex disease and several processes can be selected as a target for PET imaging. The use of PET with several different tracers has been mainly evaluated in the research setting to investigate disease pathophysiology (i.e. phenotypes, monitoring of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 144 publications
(209 reference statements)
0
35
0
1
Order By: Relevance
“…The results of this study have shown that nonenhanced MS lesions could be further classified into two patterns by k ex mapping, suggesting that k ex may be an alternative endogenous MRI contrast for separating slowly expanding MS lesions (chronic active lesions) from inactive ones. Recently, other imaging tracers and approaches based on specific pathology were also proposed to separate the nonenhanced MS lesions, such as positron emission tomography (PET) with 11C‐(R)‐PK11195, an isoquinoline carboxamide that binds selectively to the peripheral benzodiazepine receptor (targeting activated microglia or macrophages), and SWI (targeting abnormal iron deposit) 15,38,39 . With k ex MRI (potentially targeting ROS), the stage of Gd‐negative lesions may be further characterized for the better determination of the DIT of MS lesions, encouraging further validation by comparison with other imaging approaches and studies in preclinical MS models.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study have shown that nonenhanced MS lesions could be further classified into two patterns by k ex mapping, suggesting that k ex may be an alternative endogenous MRI contrast for separating slowly expanding MS lesions (chronic active lesions) from inactive ones. Recently, other imaging tracers and approaches based on specific pathology were also proposed to separate the nonenhanced MS lesions, such as positron emission tomography (PET) with 11C‐(R)‐PK11195, an isoquinoline carboxamide that binds selectively to the peripheral benzodiazepine receptor (targeting activated microglia or macrophages), and SWI (targeting abnormal iron deposit) 15,38,39 . With k ex MRI (potentially targeting ROS), the stage of Gd‐negative lesions may be further characterized for the better determination of the DIT of MS lesions, encouraging further validation by comparison with other imaging approaches and studies in preclinical MS models.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, by measuring both volumetric and dynamic quantitative means (lesions and atrophy), different MRI phenotypes of individual patients can be described by MRI-categorization ( 152 ) which could be an important component of DTMS. In addition to MRI, data obtained through other imaging biomarkers such as OCT ( 153 ) or Positron emission tomography ( 154 ) can be used as well.…”
Section: Concept Of Digital Twins In the Management Of Multiple Sclerosismentioning
confidence: 99%
“…Reprinted from EJNMMI Radiopharmacy and Chemistry Vol. 4, Issue 1, P6, 8 April 2019 [ 120 ]. Copyright: © 2021, with permission from Springer Open.…”
Section: Figurementioning
confidence: 99%